Acute kidney injury and undiagnosed immunoglobulin A nephropathy after dabigatran therapy. Issue 3 (3rd July 2018) - Jansky, Laurie; Mukkamala, Pallavi; Jebakumar, Deborah; Rao, Arundhati; Goldson, Tove M.; Forjuoh, Samuel N.
ABSTRACT: Dabigatran, a new oral anticoagulant, is a direct thrombin inhibitor used as an alternative to warfarin to reduce the risk of stroke and systemic embolism with nonvalvular atrial fibrillation. We report a case of a man who resumed dabigatran after 6 weeks of prior therapy and began experiencing hematuria with worsening kidney function. Renal biopsy with immunofluorescence and electron microscopy showed mesangial deposits consistent with immunoglobulin A nephropathy. With discontinuation of dabigatran and addition of methylprednisolone, the gross hematuria cleared and urine output improved.